Skewed Differentiation of Circulating Vγ9Vδ2 T Lymphocytes in Melanoma and Impact on Clinical Outcome. - Francesca Toia; Simona Buccheri; Ampelio Anfosso; Francesco Moschella; Francesco Dieli; Serena Meraviglia; Adriana Cordova (PLoS ONE, 2016)
OBJECTIVE:The aim of this study was to evaluate over time circulating γδ T lymphocytes in melanoma patients in terms of frequency, effector functions, and relationship with clinical stage and evolution, by comparing preoperative values to those obtained at a mean follow-up of 36 months or in the event of recurrence or disease progression, and to those of healthy controls. Also, we correlated the presence of tumor-infiltrating γδ T lymphocytes with clinical evolution of melanoma. RESULTS:Mean frequencies of circulating γδ T cells before and after melanoma removal were very similar and comparable to healthy subjects, but patients who progressed to stage III or IV showed a significantly decreased frequency of circulating Vγ9Vδ2 T cells. The distribution of Vγ9Vδ2 memory and effector subsets was similar in healthy subjects and melanoma patients at diagnosis, but circulating γδ T cells of patients after melanoma removal had a skewed terminally-differentiated effector memory phenotype. Highly suggestive of progressive differentiation toward a cytotoxic phenotype, Vγ9Vδ2T cells from patients at follow up had increased cytotoxic potential and limited cytokine production capability, while the opposite pattern was detected in Vγ9Vδ2T cells from patients before melanoma removal. CONCLUSIONS:Follow-up data also showed that tumor infiltrating γδ T cells were significantly associated with lower mortality and relapse rates, suggesting that they may serve as a prognostic biomarker, for human melanoma.